ANALISIS FAKTOR-FAKTOR PRODUKSI YANG MEMPENGARUHI INDUSTRI CRUDE PALM OIL (CPO) DI KABUPATEN ROKAN HILIR (STUDI KASUS PT. SAWIT RIAU MAKMUR) - Meri Handayani; Wahyu Hamidi; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the factors that influence the production of Crude Palm Oil (CPO), conditions of business scale and how the level of the efficient use of capital, raw materials and labor in PT. Sawit Riau Makmur in the District Rokan Hilir.Data analysis method used in this research is quantitative descriptive, where all the values of the variables obtained transformed in natural logarithm and continued by analyzing data partially and simultaneously.Factors that influence the production of palm oil industry is capital factors, raw materials and labor in PT. Sawit Riau Makmur Rokan Hilir. It can be seen from the coefficient of determination (R2) of 0.980, meaning that the capital, raw materials and labor jointly affect the industrial production of CPO in PT. Sawit Riau Makmur Rokan Hilir by 98.0%, while 2% are influenced by other factors were not analyzed.Based on the results of multiple linear regression showed that capital variables have the most influence on the industrial production of Crude Palm Oil (CPO) in the PT. Sawit Riau Makmur with a coefficient of 2.060. This means that any capital increase of one unit of production would increase by 2.060.Keywords : Production, Capital, Raw Material and Labor